Alternative Audit Quality Assessment In Overcoming Audit Tenure: Alternatif Penilaian Kualitas Audit Dalam Mengatasi Audit Tenure - Rahayu , Ruci Arizanda; Hariyanto, Wiwit; Maryanti, Eny (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine how the independence and experience of auditing as an alternative to assessing audit quality and overcoming audit tenure at KAP Subagyo & Luthfi. The method used in this research is an exploratory case study. The data collection method used is documentation, observation, and unstructured interviews. The data analysis technique used in this research is the pattern match technique. The results obtained indicate that independence and audit experience can be used as an alternative to assessing audit quality. In addition, independence and audit experience can overcome the existence of audit tenure.